Equilibrium exchange rate models and exchange rate misalignment in ASEAN countries, China, Japan and Korea - Johari, Mohamad Shukri (2018)
The misalignment of exchange rates among ASEAN, China, Japan and Korea (henceforth Plus Three Countries) has been seriously debated over the past few decades. In order to better understand the behaviour of exchange rates for ASEAN Plus Three, this study focuses on three objectives. First, to examine the roles of macroeconomics fundamentals on the real exchange rates; second, to evaluate the misalignment of exchange rates; and third, to evaluate and determine the best model to represent the exchange rates behaviour for these countries, using FEER, NATREX and BEER models. This study uses exchange rates as the dependent variable. The independent variables consist of productivity differences, net foreign assets, government spending, terms of trade, openness, real interest differences, current account, output gaps, total factor productivity, dependency ratio of the young, real interest rate, and tax revenue and foreign direct investment. To achieve the goal, Autoregressive Distributed Lag (ARDL) was used, along with the Hausman test based on Dynamic Panel Data, and model evaluation based on forecasting techniques. The results suggest that the macroeconomics fundamental variables have different impact on the exchange rates. This study demonstrates the misalignment of exchange rates using the residuals of estimation. It could imply that the currency would experience undervaluation if the disequilibrium error has positive value, and overvaluation if the disequilibrium error is negative. Next, the results from forecasting techniques based on “out-of-sample predictions” and “forecast encompassing” suggest that FEER, NATREX and BEER models are able to represent what is the best model for each different country in this region. Finally, this study suggests that the policy makers should take into account the macroeconomic indicators in order to explain exchange rate movement and subsequently achieve economic goals. Besides, ASEAN Plus Three countries should take into consideration the possibility of the formation of such a currency union as the European Union (EU) countries. On thought of that, the Chinese yuan (or renminbi) or the Japanese yen could be the anchor currency due to its have large currency coverage areas and more stable.